Positive Reinforcement Untuk Meningkatkan Kemampuan Membaca Nyaring - Dyansatithi, Nusareshi; Hasanah, Muhimmatul (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2024)
Reading is a basic ability that every individual must have. With the ability to read, individuals can express thoughts or ideas for their aims and objectives. One of the reading skills is reading aloud. This research aims to apply positive reinforcement techniques to improve the ability to read aloud using flashcard media. The subjects in this study were fourth grade elementary school boys with poor ability to read aloud. The research method used is quantitative with an experimental approach. The research design used is Single Subject Research (SSR) with a single subject. Data collection techniques use observation and reading aloud indicator assessment sheets. The data analysis used is quantitative descriptive in the form of graphic analysis. The results of the study showed that there was a positive influence of positive reinforcement techniques using flashcard media on the ability to read aloud as shown by the increase in scores from the initial baseline (A1) by 5 to 8 at the final baseline (A2).